Shaping techniques to increase independence in children with intellectual disabilities - Prinanda, Jovita Nabila (Procedia : Studi Kasus dan Intervensi Psikologi, 2024)
Intellectual disability disorder that appears during development and includes deficits in intellectual, adaptive, and social functions. These deficits can cause problems for children, including a lack of independence. This research aims to increase the ability to wear button-down t-shirts in children with intellectual disabilities. The subject in this study was an eight-year-old boy. The assessment methods used are interview, observation, psychological tests, Stanford-Binet test, Color Progressive Matrices (CPM), and Vineland Maturity Social Scale (VSMS). The shaping technique, carried out over nine sessions, can consistently increase children's independence in wearing button-up t-shirts. Parental support that gives children opportunities to do things independently also influences the success of this intervention. Gangguan disabilitas intelektual yang muncul selama perkembangan dan mencakup defisit fungsi intelektual, adaptif, dan sosial. Defisit tersebut dapat menimbulkan masalah bagi anak, termasuk kurangnya kemandirian. Penelitian ini bertujuan untuk meningkatkan kemampuan memakai kaos berkancing pada anak tunagrahita. Subjek dalam penelitian ini adalah seorang anak laki-laki berusia delapan tahun. Metode penilaian yang digunakan adalah wawancara, observasi, tes psikologi, tes Stanford-Binet, Color Progressive Matrices (CPM), dan Vineland Maturity Social Scale (VSMS). Teknik shaping yang dilakukan selama sembilan sesi secara konsisten dapat meningkatkan kemandirian anak dalam mengenakan kaos berkancing. Dukungan orang tua yang memberikan kesempatan anak untuk melakukan berbagai hal secara mandiri juga mempengaruhi keberhasilan intervensi ini.